Utilisation of blood, chicken offal and fish meal as cockerels' dietary supplements - S. O., Nwokoro (Universiti Putra Malaysia Press, 2003)
An experiment was undertaken to investigate the performance of 16-20 week-old cockerels fed diets based on three oil seed cakes viz. groundnut cake (CNG), CNG/Palm kernel cake, CNG/cotton seed cake supplemented with four sources of methionine and lysine viz. synthetic sources, blood meal, fish meal or chicken offal meal in 3 x 4 factorial treatment. The results indicated that weight gain, feed to gain ratio, nitrogen retention, liver nitrogen and liver fat as well as SCPT were not significantly (P<0.05) different either due to plant protein sources or methionine and lysine supplementation forms or both. However, the values for the serum total protein, SCOT, dressing percentage and abdominal fat were significantly (P>O. 05) affected l7y dietary treatments.